2019
DOI: 10.1021/acsomega.9b00905
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride Nanosheets Decorated Flower-like NiO Composites for High-Performance Triethylamine Detection

Abstract: The graphitic carbon nitride (g-C 3 N 4 ) nanosheets decorated three-dimensional hierarchical flower-like nickel oxide (NiO) composites (NiO/g-C 3 N 4 , Ni/CN) were synthesized via a facile hydrothermal method combined with a subsequent annealing process. The structure and morphology of the as-prepared Ni/CN composites were characterized by X-ray diffraction, field-emission scanning electron microscopy, transmission ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The In/Ni-MOF-derived In 2 O 3 -NiO-based sensors exhibit excellent stability after 26 days testing at 15 ± 5% RH. Table summarizes the comparison between this work and other TEA sensors. By comparing with previous publications, it can be found that the In 2 O 3 -NiO-based sensor possesses lower operating temperature, higher sensitivity, and lower detection limit to TEA.…”
Section: Resultsmentioning
confidence: 85%
“…The In/Ni-MOF-derived In 2 O 3 -NiO-based sensors exhibit excellent stability after 26 days testing at 15 ± 5% RH. Table summarizes the comparison between this work and other TEA sensors. By comparing with previous publications, it can be found that the In 2 O 3 -NiO-based sensor possesses lower operating temperature, higher sensitivity, and lower detection limit to TEA.…”
Section: Resultsmentioning
confidence: 85%
“…As compared with the pure WO 3 sensor, whose peak response is 4.3 at 170 ℃, the sensor based on the 0.4-Bi 2 O 3 /WO 3 composite exhibits a much higher response (2.1-fold) to the TEA at a lower operating temperature (30 ℃-decrement), revealing the advantage of the Bi 2 O 3 /WO 3 composite in TEA detection. Herein, the performances of recent TEA sensors based on various metal oxides are compared [37][38][39][40][41][42][43][44][45][46], as summarized in Table 1. There is no doubt that the Bi 2 O 3 /WO 3 sensor possesses the ideal gas-sensing characteristics, including high response and low power consumption.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally believed that the sensing mechanism of MOF gas sensors is based on the influence of gas molecule adsorption/desorption on resistance changes [ 32 , 33 ]. Some researchers also believe that oxygen molecules (O 2 ) in the air form oxygen ions (O 2 − ) by absorbing electrons on the active site of MOFs at a specific temperature.…”
Section: Resultsmentioning
confidence: 99%